3D Printing in the Mathematics Classroom: Results from a Pilot Study with Advanced Middle School Students. (December 2022) - Szymanski, Antonia; Paganelli, Andrea; Tassell, Janet
This mixed-methods study focused on advanced student engagement, mathematics competence, and the influence of teachers in classrooms that used 3D printing to teach mathematics. Quantitative methods were used to understand changes in student perceptions of competence, engagement, and feelings regarding group work. Qualitative methods were used to explore teacher self-efficacy in teaching using Prototype Problem Solving and 3D modeling. The results indicated positive changes in student disengagement. It also highlighted the influence of teachers in implementing new pedagogy in the classroom as significant differences were found between groups of students based on school. The teacher participants indicated that in addition to learning how to use 3D modeling and printing in their classrooms, using Prototype Problem Solving Activities and the professional development that they received in this program inspired them to provide more creative opportunities when teaching mathematics in a heterogeneous classroom.